Berlin for young people 2016 - Azadolmolki-Coisel, Achkan HerausgeberIn; Herden, Martin; Karlipp, Jörn; Liu, Yan; Ortner, Christoph; Schallock, Mikael; Schallock, Madeleine; Stiller, Kerstin; Trillen, Thomas; Ulbrich, Stephanie; Franzke, Stefan; Nachama, Andreas; et al. (Herden-Studienreisen, 2016)
280 pages of useful information, city maps, subjective impressions, insider tips and a comprehensive address section. Since 1996 Herden Studienreisen Berlin offers experienced and qualified tourist guides for a round trip or walking tour